Paradoxes of authentic leadership - Silva, Patricia (2021)
The dissertation explores contradictory elements of Authentic Leadership (AL) in three studies: a systematic critical review of AL research, a qualitative study leveraging a cross-national sample of 46 leaders, and a quantitative study of 305 voters in a political community. Our findings contribute to extend knowledge of the current state of research in AL, of the individual-level experience of tensions related to authenticity in leadership, revealing a new concept of the ‘undesired evolving self’ and uncovering the fact that individuals’ perception of authentic leadership is biased by shared values, which may get leaders to fall into a paradoxical loop of opposite forces that are impossible to reconcile.